Eloise started to solve a radical equation in this way: Square root of negative 2x plus 1 − 3 = x Square root of negative 2x plu s 1 − 3 + 3 = x + 3 Square root of negative 2x plus 1 = x + 3 Square root of negative 2x plus 1 − 1 = x + 3 − 1 Square root of negative 2 x = x + 2 ( Square root of negative 2 x )2 = (x − 4)2 −2x = x2 − 8x + 16 −2x + 2x = x2 + 8x + 16 + 2x 0 = x2 + 10x + 16 0 = (x + 2)(x + 8) x + 2 = 0 x + 8 = 0 x + 2 − 2 = 0 − 2 x + 8 − 8 = 0 − 8 x = −2 x = −8 Both solutions are extraneous because they don't satisfy the original equation. What error did Eloise make?
1 answer:
She kept the + 3 on the right side of the equation in her second step, she forgot to eliminate it..... there fore, it would have been -2x + 1 = x + 3 not -2x + 1 - 3 +3 = x+3
You might be interested in
Answer:
x=2,y=-3
Step-by-step explanation:
detailed explanation showed in the image above
Answer:
1
Step-by-step explanation:
-5 is a constant because its a number on its own without a variable
Answer:
11
Step-by-step explanation:
3+(−3)^2−(9+7)^0
=3+9−(9+7)^0
=12−(9+7)^0
=12−16^0
=12−1
=11
any number to the power of 0 is ALWAYS 1
Answer:
7.157894736842105263
Step-by-step explanation:
(calculator)